2013
DOI: 10.1177/0145721713484812
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Prediabetes Nutrition Shared Medical Appointments

Abstract: As demands on health care providers continue to rise, finding innovative ways to manage the patient load while providing quality health care is increasingly important. SMA health outcomes were equivalent to individual counseling outcomes, while increasing the provider's productivity by treating 6 to 8 people with prediabetes in 90 minutes compared to 1 patient in 60 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(82 citation statements)
references
References 30 publications
(45 reference statements)
0
57
0
Order By: Relevance
“…80% of eligible patients) this still means that alternative provision, by which we would typically mean an individual consultation plus some type of information provision, is still being required by one in every five patients. A recent trial found an enrolment percentage of only 31% 64 -and this was with the prospect of 50% of the patients receiving usual care. Alternatively, if group clinics are mandatory as the only type of provision, this would yield a significantly large proportion of patients who would be being treated either inappropriately (e.g.…”
Section: Acceptability and Sustainabilitymentioning
confidence: 96%
See 4 more Smart Citations
“…80% of eligible patients) this still means that alternative provision, by which we would typically mean an individual consultation plus some type of information provision, is still being required by one in every five patients. A recent trial found an enrolment percentage of only 31% 64 -and this was with the prospect of 50% of the patients receiving usual care. Alternatively, if group clinics are mandatory as the only type of provision, this would yield a significantly large proportion of patients who would be being treated either inappropriately (e.g.…”
Section: Acceptability and Sustainabilitymentioning
confidence: 96%
“…many-to-many interaction) was reported in 14 studies. 63,64,66,68,70,71,[73][74][75][76][77]82,85,86 Eleven studies explicitly reported health education/information presentation(s) by individual clinicians, 57,60,65,[66][67][68]70,71,[73][74][75]79 with one for health education/information presentation(s) by multiple clinicians 63 and two for health education/information via booklet, leaflet or video. 70,80 Seven studies reported medication review and four describe completion of prescriptions.…”
Section: Intervention Componentsmentioning
confidence: 99%
See 3 more Smart Citations